Imaging Thermoelectric Properties at the Nanoscale - Grauby, Stéphane (Nanomaterials (Basel), 2021)
Based on our previous experimental AFM set-up specially designed for thermal conductivity measurements at the nanoscale, we have developed and validated a prototype which offers two major advantages. On the one hand, we can simultaneously detect various voltages, providing, at the same time, both thermal and electrical properties (thermal conductivity, electrical conductivity and Seebeck coefficient). On the other hand, the AFM approach enables sufficient spatial resolution to produce images of nanostructures such as nanowires (NWs). After a software and hardware validation, we show the consistency of the signals measured on a gold layer on a silicon substrate. Finally, we demonstrate that the imaging of Ge NWs can be achieved with the possibility to extract physical properties such as electrical conductivity and Seebeck coefficient, paving the way to a quantitative estimation of the figure of merit of nanostructures.